Retracted:Phytochemical screening, antimicrobial activity and cytotoxicity of medicinal plant extracts: Platycarpha glomerata and Tulbaghia alliacea - Thumeka Tiwani (International Journal of Phytomedicine, 2020)
Retracted:Phytochemical screening, antimicrobial activity and cytotoxicity of medicinal plant extracts: Platycarpha glomerata and Tulbaghia alliacea